Hubungan Nilai Tanggung Jawab dalam Komunikasi Pendidikan Islam dengan Tingkat Kemandirian Belajar Mahasantri di Ma’had Al-Jami’ah Uin Sunan Gunung Djati Bandung - Maslani; Ainul Mardhiyyah; Syahruramadhan; Sheila Mafaizah; Siti Fatimatuzzahro; Paisal Ahmad Akbar (Jurnal Dakwah dan Komunikasi, 2025)
This study aims to analyze the relationship between the value of responsibility in Islamic educational communication and the level of learning independence among first-semester mahasantri at Ma’had Al-Jami’ah UIN Sunan Gunung Djati Bandung. This research employed a quantitative method with data collected through a Likert-scale questionnaire administered to 50 mahasantri. Descriptive analysis showed that the average score of responsibility was 62.56 and learning independence was 57.44, with standard deviations of 4.65 and 5.19, respectively. The Shapiro–Wilk normality test indicated that both variables were normally distributed (Sig. > 0.05), while the linearity test confirmed a significant linear relationship between the variables (Sig. = 0.000). Hypothesis testing using the Product Moment correlation revealed an rxy value of 0.537, exceeding the critical value (rtabel = 0.279) at a 5% significance level. This indicates a positive, significant, and moderate relationship between responsibility in Islamic educational communication and learning independence. The coefficient of determination (r² = 0.2884) shows that responsibility contributes 28.84% to learning independence. The t-test further supports these findings, with thitung = 4.41 surpassing ttabel = 2.01, leading to the acceptance of the alternative hypothesis (Hₐ). In conclusion, this study demonstrates that the value of responsibility in Islamic educational communication plays a crucial role in shaping the learning independence of mahasantri. These findings reinforce the Self-Regulated Learning theory, which asserts that responsibility is a fundamental foundation in the development of individual learning autonomy. Keywords: Responsibility, Islamic Educational Communication, Learning Independence